2015
DOI: 10.3389/fcimb.2015.00003
|View full text |Cite
|
Sign up to set email alerts
|

Milk- and solid-feeding practices and daycare attendance are associated with differences in bacterial diversity, predominant communities, and metabolic and immune function of the infant gut microbiome

Abstract: The development of the infant intestinal microbiome in response to dietary and other exposures may shape long-term metabolic and immune function. We examined differences in the community structure and function of the intestinal microbiome between four feeding groups, exclusively breastfed infants before introduction of solid foods (EBF), non-exclusively breastfed infants before introduction of solid foods (non-EBF), EBF infants after introduction of solid foods (EBF+S), and non-EBF infants after introduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
205
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(223 citation statements)
references
References 67 publications
14
205
3
1
Order By: Relevance
“…Many studies have reported that BF infants are colonized with higher proportions of microbes from the phylum Actinobacteria and less Firmicutes than FF infants. 23,25,26,28,33 Other studies report that BF infants have similar levels of Actinobacteria and Firmicutes 28,30 but lower proportions of Bacteroidetes 31,36 and Proteobacteria 26,28 compared to FF infants.…”
Section: (Finland)mentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have reported that BF infants are colonized with higher proportions of microbes from the phylum Actinobacteria and less Firmicutes than FF infants. 23,25,26,28,33 Other studies report that BF infants have similar levels of Actinobacteria and Firmicutes 28,30 but lower proportions of Bacteroidetes 31,36 and Proteobacteria 26,28 compared to FF infants.…”
Section: (Finland)mentioning
confidence: 99%
“…Several studies found bifidobacteria to be significantly greater in BF infants 18,23,26,28,33,36,37,39,47,51 ; Fan and colleagues 26 reported roughly double the relative abundance of bifidobacteria in BF than FF infants. Bifidobacteria have been shown to account for 70% of the sequences of exclusively breastfed (EBF) infants 40 and appear earlier in the feces of EBF than in FF infants 38 In addition, infants who were exclusively breastfed in early life maintained greater colonization with bifidobacteria later in infancy.…”
Section: (Finland)mentioning
confidence: 99%
See 3 more Smart Citations